INTERNATIONAL STANDARDS FOR THE PROTECTION OF THE RIGHT TO FREEDOM OF PEACEFUL ASSEMBLY AND FREE ASSOCIATION OF BULGARIANS IN THE REPUBLIC OF NORTH MACEDONIA - Valcheva, Alexandra (E-Journal VFU, 2025)
The right to freedom of peaceful assembly and free association has an essential role for the functioning of democratic societies, which is why it is recognized in the main international acts for the protection of human rights and freedoms. The international community regulated this right already in the Universal Declaration of Human Rights and subsequently reaffirmed its importance by including it in the content of a number of other international universal and regional treaties. The adoption of explicit standards and mechanisms for the protection of the right to freedom of peaceful assembly and free association provides conditions for its effective exercise by all citizens, as well as an opportunity through its implementation for them to exercise public control over the activities of public entities. Despite the recognized importance of the analyzed law at the international, European and national level, in the last year there have been more and more cases of its violation against the Bulgarian minority in the Republic of North Macedonia. The complex interstate relations between the Republic of Bulgaria and the Republic of North Macedonia, however, should not be a reason for not respecting the personal rights of citizens, regardless of their nationality. Decisive measures need to be taken at both national and European level to fully guarantee the fundamental rights and freedoms of minority groups in EU member states and in countries that have candidate status for membership in the European Union unification.